Implications of the Emerging Home Systems Technologies on Rehabilitation and the HS-ADEPT Project - Martyn Cooper (1995)
This paper gives a review of the current and anticipated developments in Integrated Home Systems and raises the implications these have in the field of rehabilitation. Firstly, the systems under consideration are defined and their development world-wide outlined. An overview of the European Home Systems Specification is given. The implications of this technology for rehabilitation are then raised and an outline is given of the TIDE Project HS-ADEPT (Home Systems - Access for Disabled and Elderly People to this Technology). Concluding comments are offered in the hope of stimulating the necessary interdisciplinary discussion.